Fractal approaches for modeling financial assets and predicting crises - Nekrasova, Inna 1962-; Karnaukhova, Oxana; Christiansen, Bryan 1960- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores fractal structure and long-term memory of the financial markets to predict prices of financial assets and financial crisis. It identifies the criteria to select financial assets for investment and the creation of a randomized algorithm of R/S-analysis, which allows to give a more accurate assessment of the fractal dimension in the financial markets"...
Keywords: Finance -- Mathematical models; Fractals